Targeting the pericyte antigen DLK1 with an alpha type-1 polarized dendritic cell vaccine results in tumor vascular modulation and protection against colon cancer progression - McCormick, Amanda L.; Anderson, Trevor S.; Daugherity, Elizabeth A.; Okpalanwaka, Izuchukwu F.; Smith, Savanna L.; Appiah, Duke; Lowe, Devin B. (Frontiers in Immunology, 2023)
Despite the availability of various treatment options, colorectal cancer (CRC) remains a significant contributor to cancer-related mortality. Current standard-of-care interventions, including surgery, chemotherapy, and targeted agents like immune checkpoint blockade and anti-angiogenic therapies, have improved short-term patient outcomes depending on disease stage, but survival rates with metastasis remain low. A promising strategy to enhance the clinical experience with CRC involves the use of dendritic cell (DC) vaccines that incite immunity against tumor-derived blood vessels, which are necessary for CRC growth and progression. In this report, we target tumor-derived pericytes expressing DLK1 with a clinically-relevant alpha type-1 polarized DC vaccine (αDC1) in a syngeneic mouse model of colorectal cancer. Our preclinical data demonstrate the αDC1 vaccine's ability to induce anti-tumor effects by facilitating cytotoxic T lymphocyte activity and ablating the tumor vasculature. This work, overall, provides a foundation to further interrogate immunemediated mechanisms of protection in order to help devise efficacious αDC1-based strategies for patients with CRC.